EXTRACTION, PROPERTIES AND USE OF STYRENE - Shaydullayeva Shohista Shaymardan qizi; Abdullayeva Farida (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Styrene, a versatile and essential monomer, plays a crucial role in the synthesis of various polymers. This article delves into the extraction, chemical properties, and wide-ranging applications of styrene. The literature analysis explores historical perspectives and recent advancements, while the methods section provides insights into extraction techniques. The results section discusses the outcomes of polymerization processes, leading to the formation of diverse products. The discussion section evaluates the implications of styrene use, including health effects and environmental considerations. The article concludes with key takeaways and suggestions for future research.